Amino acid modified hyperbranched poly(ethylene imine) with disaccharide decoration as anionic core–shell architecture: Influence of the pH and molecular architecture on solution behaviour. (2nd December 2015) - Striegler, Christin; Franke, Markus; Müller, Martin; Boye, Susanne; Oertel, Ulrich; Janke, Andreas; Schellkopf, Leonard; Voit, Brigitte; Appelhans, Dietmar
Abstract: Dendritic polymers represent a class of materials for prospective drug delivery application. For that purpose we present the synthesis and characterization of hydrophilic, anionic core–shell architectures based on poly(ethylene imine) (PEI) as core molecule and polyamino acid chains (composed of glutamic acid or aspartic acid) as shell component. NCA polymerization is used for coupling polyamino acid chains to PEI scaffold. Modifying these structures with sugar molecules result in the formation of new core–shell architectures combining a mixture of binary and double shell. For their potential biomedical applications the solution properties of these anionic core–shell architectures at various pH values (3–9) were studied by different analytical tools (zeta potential, streaming potential pH titration, DLS, AFM, in-situ AFM, TEM and cryo-TEM). Especially, the sugar-decorated core–shell architectures mainly provide isolated macromolecules over a broad pH range. Furthermore, the anionic core–shell architectures are suited to interact with cationic molecules. Graphical abstract: Highlights: Hydrophobic and α-helical polymeric benzyl glutamate chains are attached to cationic poly(ethylene imine) core molecules. From this anionic core–shell architectures combining binary and double shell are established. Maltose and lactose are the second shell component. Preferably, isolated macromolecules are observable over a broad pH range (3–9).